Analisis laporan keuangan UMKM berdasarkan Standar Akuntansi Keuangan Entitas Mikro, Kecil dan Menengah (SAK EMKM) pada CV. Eka Niaga - Andayani, Ni Made Sri; Wangkar, Anneke; Pinatik, Sherly (Riset Akuntansi dan Manajemen Pragmatis, 2024)
A financial report is the definitive account of a company's financial position. It is a crucial tool for Micro, Small and Medium Enterprises (MSMEs) in particular. Financial report for MSME actors provides a clear picture of financial positions, including assets, debts, income, and expenses. MSMEs must prepare their financial reports in accordance with the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM), issued by DSAK IAI. This standard is designed to streamline the financial reporting process for MSMEs. This study will determine the financial statements of CV. Eka Niaga. This study will determine the financial statements of CV. Eka Niaga based on Eka Niaga, which is based on SAK EMKM. It will also identify the obstacles experienced by CV. Eka Niaga's financial reporting is based on SAK EMKM. This research employs a descriptive qualitative method, using both primary and secondary data. The results of this research clearly show that the financial statements of CV. Eka Niaga do not meet the requirements of SAK EMKM. The obstacles experienced by CV. Eka Niaga in financial reporting based on SAK EMKM are due to a lack of understanding of SAK EMKM, a lack of socialization of SAK EMKM, and a lack of human resources in the accounting field.